Penerapan Indeks Beneish Ratio Pada Identifikasi Kecurangan Laporan Finansial Pada Perusahaan Publik dalam Konteks COVID- 19 dan Sesudahnya - Nduru, Yitro Carol; Lubis, Arfan Ikhsan (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This study aims to investigate the potential impact of COVID-19 on financial fraud across different industries. The Ministry of Manpower's survey data, which indicated that 88% of businesses were impacted by the pandemic, served as the basis for this research. Quantitative approaches are employed in this study. This study's population consists of companies registered on the Indonesian Stock Exchange during 2020 and 2022, and 40 financial statement samples overall, drawn from 10 different companies. The Beneish M-Score test is employed. According to the study's findings, businesses are morally obligated to keep accurate financial records, and COVID-19 has no discernible impact on the amount of financial fraud.